Esterifikasi Gliserol dengan Asam Laktat Menggunakan Lipase yang Diamobilisasi dalam Karagenan - dewi luthfiana; Anna Roosdiana; Sutrisno (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The source of alcohol in this experiment was glycerol and the source of carboxylic acid compound was lactic acid. This experiment aimed to determine optimum conditions of reaction time, and molar ratio, and to characterize the resulted ester between glycerol and lactic acid toward esterification using immobilized lipase Candida rugose in carrageenan. The identification of glyceryl lactic based on FTIR spectroscopy and the characterization based on HLB value. Esterification of glycerol and lactic acid used methylene chloride solvent with the reaction time (6, 12, 18, 24, and 30) hours and the molar ratio of (1:1, 1:2, 1:4, 1:6, and 1:8) mmol. The optimum condition can be seen from the highest percent conversion value from variations of each parameter used. The result showed that the optimum condition of esterification was reached at 30 hours with a 1:4 ratio of lactic acid: glycerol resulting in 42,49% of the conversion value. Theoretically, the resulted ester was identified by FTIR spectroscopy proven with a wavenumber shift and intensity changes in the FTIR spectrum, then compared to the FTIR spectrum of glycerol and pure lactic acid. There is a stretching vibration of C=O in the wavenumbers 1750-1700 cm-1 and 1300-1000 cm-1 which is characteristic of the stretching vibration of C-O ester. The HLB ester value of lactic acid (monoglyceride) is in the range of 7-8 which is a type of wetting agent emulsifier.